RESEARCH ON THE INFLUENCE OF VARIOUS SUBSTANCES ON CASPASE ACTIVITY (REVIEW) - E. S. Kokareva; V. V. Morozov; Ya. M. Stanishevskiy; M. A. Zhuravleva; A. V. Zubkov (Разработка и регистрация лекарственных средств)
The paper presents an overview of the structure and functions of caspase group enzymes. The main stages and ways of development of programmed cell death - apoptosis were demonstrated. The mechanisms of inhibition and activation of caspasesand their role in cell apoptosis are demonstrated. The different stages of caspase activation in the body are still insufficiently studied. At present, the structure, properties, key points of the functioning and regulation of caspases in the body have been studied in detail, but at the molecular and cellular levels it is not enough to directly regulate their activity. Modern studies of the effect of artificially created substances of different nature on these enzymes, in turn, open up prospects for further search for methods of their regulation, which in turn would allow using the knowledge gained in the treatment of oncological, autoimmune and neurodegenerative diseases.